Efficacy of codelivery of dual AAV2/5 vectors in the murine retina and hippocampus - Palfi, Arpad; Humphries, Peter; Kenna, Paul; Farrar, Gwyneth; Chadderton, Naomi (My University, 2012)
Recombinant adeno-associated virus (AAV) represents an efficient system for neuronal transduction. However, a potential drawback of AAV is its restricted packaging capacity of approximately 5kb. To bypass this limita- tion, a number of dual- and triple-vector strategies divide the transgene(s) between two or three AAVs. The success of these approaches relies directly on efficient cotransduction of the component AAVs. Although proof of concept for these stratagems has been demonstrated, the underlying cotransduction rate has not been ana- lyzed quantitatively. In this study, cotransduction efficiencies in both retina and hippocampus have been in- vestigated, using two reporter AAVs expressing either a green (GFP) or red (DsR) fluorescent protein. Transduction efficiencies were monitored via microscopy, flow cytometry, and quantitative PCR. After viral transduction with 1.5 ? 10 9 viral particles of each of the reporter AAVs, approximately one-third of the retinal cells expressed one or both transgenes at levels detectable by native fluorescence. Notably, the majority of the remaining retinal cells were also transduced and expressed the reporters at lower levels, which were detectable only by immunolabeling. Flow cytometric analysis demonstrated cotransduction rates of up to 55% with the two reporter AAVs in retinal cells. Modifying the ratio of the two coadministered AAVs resulted in altered mRNA expression levels of the two reporter genes in cotransduced cell populations. The study suggests that codelivery of AAV is an efficient means of expanding the therapeutic application of AAV in neurons.
PUBLISHED
Keywords: green fluorescent protein; messenger RNA; red fluorescent protein; virus vector; green fluorescent protein; messenger RNA; red fluorescent protein; virus vector